Ernesto Codignola: un Maestro di ieri (e non solo) - Mariani, Alessandro (Studi sulla Formazione/Open Journal of Education, 2018)
This text focuses the first phase (that between actualism and fascism), the second phase (that of disillusionment and detachment of 1929) and the third phase (that after the death of Giovanni Gentile) of the thought of Ernesto Codignola, “intellectual-pedagogist”, Master of yesterday (and not only).